(untitled) (Aporia, 2017)
The aim of this essay is to defend the thesis that Rousseau favoured popular sovereignty. Rousseau defines popular sovereignty as the “exercise of the general will” of the people, where the general will is those interests shared by the whole citizenry (Rousseau 2011, 170) . Before reaching this conclusion, I initially draw a distinction between the two ways in which Rousseau describes the function of government. On the one hand, it is described as the executive agent of the citizenry (which I call description A). On the other hand, he describes government as an independent body that may choose to prioritise its own interests (description B). Through the essay I argue that these two descriptions are incompatible, and that Rousseau’s conflation of these two descriptions has engendered confusion as to whether he did in fact support popular sovereignty. The purpose of this essay is to defend the view that Rousseau did favour popular sovereignty, despite the extensive power that he describes the government as having.